Graded YSZ/Al2O3 nanocomposite coatings fabricated by electrophoretic deposition of Al and nanosized YSZ particles - Baghshahi Saeid; Rajabi Masoud; Siahpoosh Seyed Mahdi; Esfehani Fateme (Processing and Application of Ceramics, 2024)
Yttria-stabilized zirconia (YSZ)/Al2O3 composite coatings with a compositional gradient along the film cross-section were deposited on a nickel-based superalloy by electrophoretic technique and subsequent multi-step sintering route. Aluminium powder was used to reinforce the YSZ matrix by the in situ formation of alumina during the sintering procedure. The electrostatic interaction between particles in suspensions was evaluated through zeta potential and particle size analyses. Then, electrophoretic deposition (EPD) on Inconel 718 electrodes was carried out by employing three well-dispersed suspensions, including nanostructured YSZ with 0, 30 and 50 wt.% Al particles. XRD characterization indicated that tetragonal zirconia, monoclinic zirconia and alumina mainly existed in the coating after sintering at 1150°C. Surface morphology and cross-sectional views of each layer were characterized by field emission scanning electronmicroscopy (FE-SEM). The elemental map analyses of the energy dispersive X-ray spectroscopy (EDS) technique confirmed that the YSZ content increases gradually across the sample cross-section. The mean thickness of the coating was about 200 μm. Particle size analysis by FE-SEM indicated that the majority of quasi-spherical YSZ particles on the surface had the size in nano-range after sintering at 1150°C.